Uji Aktivitas Antifungi Ekstrak Rimpang Kencur (Kaempferia galanga L.) Terhadap Saprolegnia sp. Secara In Vitro [Antifungal Activity Test Of Kaempferia galanga L. Extract To Saprolegnia sp. By In Vitro] - Rahayu Kusdarwati, Ayu Ratnaningtyas, Dewa Ketut Meles (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Saprolegnia sp. is a fungus that causes the Saprolegniasis disease can infection eggs and fresh water fish. Treatment Saprolegniasis done using chemical drugs, however the use of drugs is bad for the environment and biota. The purpose of the research was to determined the antifungal activity include a minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) from Kaempferia galanga L. to Saprolegnia sp. by in vitro. This research used 9 different concentrations of Kaempferia galanga L extract were 50%, 12.5%, 6.25%, 3.12%, 1.56%, 0.78%, 0, 39%, 0.2%, positive control used H2O2 3% and negative control used DMSO 10%. The results showed that the extract of Kaempferia galanga L had an antifungal activity were inhibits and kill with minimum inhibitory concentration (MIC) was 0.39% equivalen with 3,9 mg/ml and minimu fungicidal concentration (MBC) was 1.56% equivalen with 15,6 mg/ml. The existence of antifungal activity against Saprolegnia sp. by in vitro caused by some active compounds from the extracts of the Kaempferia galanga L. are polyphenolic compounds, flavonoin, saponins and essential oils.